EFESIENSI LAYANAN BIMBINGAN DAN KONSELING DI SMAN 1 ARONGAN LAMBALEK ACEH BARAT - Khaira, Wanty (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
The guidance and counseling program is going well so evaluation is needed. The implementation of the guidance and counseling program evaluation at SMAN 1 Arongan Lambalek aims to see the progress and obstacles experienced in the implementation of counseling programs such as the lack of additional knowledge obtained by guidance and counseling teachers from year to year, such as training, seminars and so on, and availability rooms that are not ideal so that when doing archives on the archive guidance and counseling activities are quickly broken. Because the assessment at the school level is the responsibility of the principal who is assisted by special counselors and other personnel. In addition, assessment of guidance and counseling activities is also carried out by authorized officials (Supervising guidance and counseling) from higher institutions (City / Regency education department.